Lifetime estimation and orientation effect based on long-term degradation analysis of thermoset and thermoplastic insulators - Ullah, Israr; Ullah, Rahmat; Amin, Muhammad; Abd Rahman, Rahisham; Khan, Aftab; Ullah, Nasim; Alotaibi, Sattam (MDPI, 2022)
Polymeric insulators have replaced ceramic insulators due to their obvious properties like low surface energy, which exhibits good hydrophobic performance, low weight, etc. However, electric utilities have concerns about their long-term performance. In that context, the long-term performance of two different types of polymeric insulators are investigated in this study: thermoset Silicone rubber (SiR) and thermoplastic elastomeric (TPE). Multi-stress aging was performed in the different orientations of both types of polymeric insulators. During multi-stress aging, insulators are exposed to varied loads in both vertical and horizontal orientations, simulating actual service environmental conditions. Experiments were done in a chamber where different types of stresses were simulated, which resembles the weathering conditions of Hattar, Pakistan, which is one of the most polluted industrial zones. Both insulators were stressed in a chamber under the designed weathering conditions for two years and six months at different orientations. Polymeric insulators made of SiR perform better in the vertical position than that in the horizontal position. Furthermore, the experimental results show that both materials are capable in a variety of situations. SiR, on the other hand, performed well due to its high hydrophobicity, which means it is less impacted by contaminants and hence has a longer life and higher service performance than TPE.